2017
DOI: 10.15689/ap.2017.1601.02
|View full text |Cite
|
Sign up to set email alerts
|

Normative data of the Brazilian elderly in Logical Memory subtest of WMS-R

Abstract: The aim of this study was to establish normative data for the Brazilian elderly population in the Logical Memory (LM) subtest of the Wechsler Memory Scale, revised version (WMS-R) and investigate the ability of scores in this subtest (immediate and delayed recall) to discriminate the elderly with and without depressive symptoms. The sample consisted of 334 elderly participants. Participants answered a sociodemographic and health questionnaire, the MMSE, the GDS-15, and the LM subtest. Data were analyzed by des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Although a Japanese normative study of the LM for older adults reported that the LM I and not the LM II related to educational level [25], this may be due to small sample size (n=50) and relatively narrow range of educational level (6–18 years). The significant effect of age on the performances on the LM subtest found in this study is also in line with numerous previous reports [1315,18,24,26,27]. In contrast to the effects of education and age, the effects of gender was not significant on any of the LM subtest scores, which is also consistent with the results of the previous studies conducted in other countries [15,17,25].…”
Section: Discussionsupporting
confidence: 93%
“…Although a Japanese normative study of the LM for older adults reported that the LM I and not the LM II related to educational level [25], this may be due to small sample size (n=50) and relatively narrow range of educational level (6–18 years). The significant effect of age on the performances on the LM subtest found in this study is also in line with numerous previous reports [1315,18,24,26,27]. In contrast to the effects of education and age, the effects of gender was not significant on any of the LM subtest scores, which is also consistent with the results of the previous studies conducted in other countries [15,17,25].…”
Section: Discussionsupporting
confidence: 93%
“…Kawano et al (2013) reported significant correlations between age and LM-I and LM-II scores and between education level and LM-I scores in an old–old Japanese sample. Oliveira et al (2017) found that age and education level significantly influenced all LM scores in a sample of Brazilian older adults. Vogel et al (2018) found a significant impact of education level on the LM measures but not for sex or age in a sample of healthy Danish volunteers older than 59 years.…”
Section: Discussionmentioning
confidence: 86%
“…Some limitations in the present work should be noted. (a) Some exclusion criteria from the sample were flagged as factors which can potentially influence EM performance, for example, depressive symptoms (Oliveira et al, 2017). Although we have included the three most commonly studied variables in our analysis (age, educational level, and sex), future work should extend and analyze the potential influence of other health, affective, and sociodemographic measures.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the predictor of processing speed was the education level, indicating that the more years the participant has studied, the better is her/his processing speed. Reports are proving that more years of study are positively associated with improved cognitive performance (Oliveira et al, 2017) and processing speed in older adults (Ihle et al, 2018).…”
Section: Discussionmentioning
confidence: 99%